2014
DOI: 10.1074/jbc.m114.548131
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Transducer-specific Molecular Efficacies Generate Biased Agonism at a G Protein-coupled Receptor (GPCR)

Abstract: Background: Biased agonism is an incompletely understood phenomenon describing the unequal activation of different signal transduction pathways by a G protein-coupled receptor (GPCR). Results: A cell-free approach using GPCR-transducer fusion proteins (G-protein or ␤-arrestin) quantifies signaling in vitro to elucidate the molecular basis of biased agonism. Conclusion: Differences in ligand-receptor-transducer coupling account for biased agonism in cells. Significance: Biased agonism is a bona fide molecular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
123
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(143 citation statements)
references
References 62 publications
(71 reference statements)
8
123
0
1
Order By: Relevance
“…It has been well appreciated that allosteric transducers such as heterotrimeric G proteins or β-arrestins promote high-affinity agonist binding (10,23,24). We also observed that 15 inhibited the high-affinity binding of a radiolabeled (25) that is promoted by either heterotrimeric Gs protein or β-arrestin1 (Fig.…”
Section: Resultssupporting
confidence: 57%
“…It has been well appreciated that allosteric transducers such as heterotrimeric G proteins or β-arrestins promote high-affinity agonist binding (10,23,24). We also observed that 15 inhibited the high-affinity binding of a radiolabeled (25) that is promoted by either heterotrimeric Gs protein or β-arrestin1 (Fig.…”
Section: Resultssupporting
confidence: 57%
“…In how far the two binding modes described here are connected to different conformations of holo-arrestin remains to be elucidated.Our findings correlate well with a biochemical study of the type-1 angiotensin receptor, which has shown that receptor binding to β-arrestin is less specific than its interaction with the G q α-subunit. β-arrestin binding occurred in the presence of all peptide agonists, while efficient G q binding was limited to a small subset of the ligands studied (49). Rhodopsin activation has been described extensively, facilitated by natural abundance and its photochemical properties, which provide an ideal system for biophysical and biochemical characterization.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 However; recent findings have revealed a higher mechanistic complexity of this biased compound that involves both β-arr and Gq effectors 14,19 but leads to signaling pathways different from those promoted by Ang II. 14 Interestingly, SII has demonstrated β-arr-dependent pharmacological properties, such as inotropic responses on isolated cardiomyocytes 20 ; however, its low affinity for AT1-R has prevented further in vivo characterization of its biased activity.…”
Section: Ilementioning
confidence: 99%